2012
DOI: 10.1063/1.3679133
|View full text |Cite
|
Sign up to set email alerts
|

The bound states of Fe impurity in wurtzite GaN

Abstract: A study on the bound states of Fe impurities in GaN by ultraviolet photoluminescence (PL) emissions is presented. Two elusive PL lines were observed at 3.463 eV (L1) and 3.447 eV (L2), respectively. The intensities of the two lines are proportional to the Fe concentration. The temperature dependence of L1 and L2 revealed acceptor-like and strong localized characteristic, respectively. Furthermore, Raman analysis indicated that L2 is correlated to an exciton bound to a nitride-vacancy (VN) related complex, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Hence, an Fe-V N complex structure-related Raman mode is considered. [77] 4. Progress of Na-flux grown GaN…”
Section: Si-doping For N-gan Substratementioning
confidence: 99%
“…Hence, an Fe-V N complex structure-related Raman mode is considered. [77] 4. Progress of Na-flux grown GaN…”
Section: Si-doping For N-gan Substratementioning
confidence: 99%
“…[19][20][21] In this Letter, we report our investigation on the SAW properties of thick semiinsulating Fe-doped GaN films grown by HVPE. It is found that Fe-doped GaN films exhibit lower insertion loss and higher electromechanical coupling coefficient for Rayleigh mode than non-intentionally (nid) doped GaN films.…”
mentioning
confidence: 98%
“…In this work, Fe-doped GaN epitaxial films with wurtzite structure were grown on (0001) sapphire substrate, and the crystal orientation GaN is parallel to sapphire [11][12][13][14][15][16][17][18][19][20]. Two Fe-doped GaN samples of different thickness were employed in our experiment, and their thickness are respectively 33 lm (sample 1) and 15lm (sample 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Previous PL studies analysed the infrared emissions (1.30 eV) related to Fe 3þ , 14 and the nearband-edge emission of GaN:Fe. 15 Detailed studies of the optical absorption and reflectance of GaN:Fe versus the Fe doping were also presented. 16,17 As a deep acceptors, the lifetime of PL was modulated due to carrier trapping of Fe deep acceptors in GaN:Fe.…”
mentioning
confidence: 99%